(untitled) (Research, Society and Development, 2021)
The work analyzed the application of the Realistic Simulation (SR) methodology inovation as a didactic-pedagogical strategy for the practice of entrepreneurial education in business administration. The justification is based on the observation that the teaching methodology prevalent in Business Administration courses is traditionally contentious and does not stimulate creativity and entrepreneurial manifestations in a practical way. The research that supported the realization of this work can be characterized as a qualitative approach, developed according to the method of a single case study, based on the adoption of the Realistic Simulation methodology followed by semi-structured interviews carried out on the campus of the Federal University of Viçosa. The studied universe was composed of two groups, one with undergraduate students and the other with students from the master’s program, both in UFV Administration. The main findings demonstrate that SR can be an important instrument of teaching practice capable of increasing resources used in entrepreneurial education processes in administration courses. Therefore, it is concluded that there was success in the critical-reflexive experience of active methodology as a didactic strategy in the entrepreneurial education process.